Effects of fire wood and charcoal smoking on the polycyclic aromatic hydrocarbon and fatty acid profiles of mud fish - Omodara, Niyi B.; Olabemiwo, Ojeyemi M.; Taofik A., Adedosu (Archives of Business Research, 2019)
Cooking methods have been linked with the presence of PAHs in some foods. Mud fish is one of the major components of delicacies in Western part of Nigeria. It is either cooked or smoked for consumption. Not much study has been carried out to determine the effect of methods of preparation on the level of PAHs concentration in mud fish. Fresh mud fish was purchased in Ogbomoso and smoked for 1, 2, 3 and 4h respectively at a temperature range of 200 oC – 210 oC with the use of Azadirachta indica wood and charcoal. A representative portion of about 10 g of sample was taken from the homogenized sample and extracted with ultrasonicator using three solvent systems: methanol, methanol: dichloromethane (1:1v/v) and dichloromethane. The aromatic and the free fatty acid fractions were subsequently analyzed with Gas Chromatography (GC/FID). PAHs and FFA were quantified and used to monitor the impact of the type of biomass used in smoking the mud fish. The result showed that 24 PAHs were detected in all the samples except in firewood smoked mud fish (FSMF) 1hr and charcoal smoked mud fish (CSMF) 1h – 4h where benzo[j]fluoranthene was below detection limit. The total PAHs found in all smoked mud fish in this study were higher than what was found in fresh [control] fish. Amount of PAHs in samples smoked with wood was significantly different from samples smoked with charcoal. The main compounds of free fatty acids present in the samples were myritic acid, palmitic acid, stearic acid and linoleic acid. The concentration of PAHs with 2 – 3 rings were less than the PAHs with 4 – 6 rings, with pyrene, benzo[c]phenanthrene and indeno(1,2,3 – cd) pyrene being the most abundant compounds. The phenanthrene/anthracene ratio for FSMF ranged from 0.27 – 9.02 and 0.72 – 1.66 for CSMF which suggests the source of the PAHs was pyrolitic. Also, Fluoranthene/fluoranthene + pyrene ratio ranged from 0.00 – 0.54 in FSMF and 0.01 – 0.99 for CSMF samples which equally suggests a pyrolytic source. From the proximate analysis results, the crude protein for the UPMF is 28.27 which increases gradually to 47.7 % in FSMF 4h and increased to 65.94 % in CSMF 4h. The crude fiber of all the samples both processed and unprocessed were generally low than expected. The percentage composition of fat increased from 1.01 % in fresh sample to 6.04 % in CSMF 4h.